Injecting buprenorphine-naloxone film: Findings from an explorative qualitative study - White, N.; Flaherty, I.; Higgs, Peter; Larance, B.; Nielsen, S.; Degenhardt, L.; Ali, R.; Lintzeris, N. (2015)
Introduction and Aims: Experiences of buprenorphine-naloxone (BNX) sublingual film injection are not well documented or understood. We examined how people who inject BNX film seek and share information about this practice, document the methods used to prepare BNX film for injection, and report participants' experiences of this practice. Design and Methods: Interviews were (n=16) conducted with people who indicated that they had injected BNX film since its introduction onto the Australian market. Semistructured interviews were recorded and transcribed. NVivo10 program (QSR International) was used to analyse the data using qualitative description methodology. Results: Participants largely reported similar BNX film preparation techniques, although the texture of BNX film during preparation to inject was reported to be unusual (gluggy), and there were many varied accounts associated with the amount of water used. Physical harms reported as associated with injecting BNX film were described (including local and systemic issues); participants reported injecting the film to enhance its immediate effects, yet generally reported that sublingual administration provided longer-lasting effects. Discussion and Conclusions: Understanding knowledge acquisition about injecting new formulations of opioid substitution therapy is crucial in developing more effective harm-reduction strategies. Dissemination by peer networks to those who are currently or planning to inject BNX film regarding the 'gelatine like' texture when mixing, using only cold water and double filtering is important to ensure safer injecting practices. Findings from this study highlight the importance of peer networks for the dissemination of harm-reduction information. Introduction of new formulations internationally requires more qualitative studies to inform safer practices.